DYNAMIC ASSESSMENT OF ELECTROCARDIOGRAPHY PARAMETERS DURING ELECTROMYOSTIMULATION IN ATHLETES - G. A. Khairetdinova; Yu. N. Fedulaev; O. N. Andreeva; V. V. Ar’kov (Российский кардиологический журнал, 2010)
In 72 patients (32 athletes at recovering stage of training and 35 patients with patello-femoral arthrosis), femoral quadriceps muscle was stimulated (Kotz current), to assess the effects on electrocardiographic parameters of vegetative disbalance. After 10 electro-stimulation procedures, there was a significant decrease in the number of supraventricular and ventricular extrasystoles, a reduction in QT interval dispersion (within the range of baseline and dynamic normal values), and an increase in circadian index. No significant change in time and spectral parameters of heart rate variability was observed; however, there was a tendency towards a greater reduction in vegetative disbalance among athletes.